2018
DOI: 10.1177/1010428318810059
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between chemokines CCL2, CCL3, and CCL4 with the tumor microenvironment and tumor-associated macrophage markers in colorectal cancer

Abstract: A complex network of chemokines can influence cancer progression with the recruitment and activation of hematopoietic cells, including macrophages to the supporting tumor stroma promoting carcinogenesis and metastasis. The aim of this study was to investigate the relation between tissue and plasma chemokine levels involved in macrophage recruitment with tumor-associated macrophage profile markers and clinicopathological features such as tumor-node-metastases stage, desmoplasia, tumor necrosis factor-a, and vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
71
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(80 citation statements)
references
References 55 publications
6
71
1
2
Order By: Relevance
“…The expression levels of CCL4 are increased in tumor compared with healthy tissues. The higher levels of CCL4 in plasma are associated with poor prognosis (25). Although the expression levels of CCL2, CCL3, RANTES/CCL5 and CCL17 were not downregulated in the present study, these chemokines can also participate in colon cancer progression (25)(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 47%
“…The expression levels of CCL4 are increased in tumor compared with healthy tissues. The higher levels of CCL4 in plasma are associated with poor prognosis (25). Although the expression levels of CCL2, CCL3, RANTES/CCL5 and CCL17 were not downregulated in the present study, these chemokines can also participate in colon cancer progression (25)(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 47%
“…While MK2 was found to be significantly associated with a long list of cytokines and chemokines amongst gastric cancer patients including IL1-β, GM-CSF, TNFa, IL-6, Mip-1β, IFN-α2, MCP-1, G-CSF, and IL-2; it was only significantly associated, after the Sidak correction for multiple testing, with Mip-1β among those who metastasized, revealing a new link to gastric metastasis. Studies by other groups have suggested pro-metastatic activity of Mip-1β [22,23], but there has also been suggestions otherwise [24]. Thus, more in depth mechanistic studies are needed to assess the overall impact of this chemokine in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…24 Excessive production of CCL2 has been demonstrated in multiple cancer or precancerous lesions including oral lesions. 25,26 Up to date, most studies have been focused on how CCL2 promotes cancer progression by recruiting inflammatory cells in lung cancer, 10 colorectal cancer, 11 breast cancer, 12 and oral cancer. 14 However, there is still a lack of evidence that the origin of local CCL2 in tumor microenvironment and its direct effect on tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…CCL2 and its main chemokine receptor CCR2 have been implicated in the pathogenesis of several different disease processes, including neurological disorders, autoimmune disease, obesity, atherosclerosis, and cancer. 9 Significantly high expression of CCL2 has been detected in the epithelial region of many tumor types, including lung cancer, 10 colorectal cancer, 11 and breast cancer. 12 CCL2 promotes tumor progression through multiple mechanisms including recruiting of CCR2-positive mononuclear macrophages to secret of a variety of inflammatory factors and to promote angiogenesis.…”
mentioning
confidence: 99%